2013
DOI: 10.4103/1596-3519.117626
|View full text |Cite
|
Sign up to set email alerts
|

Corneal ulcers in a tertiary hospital in Northern Nigeria

Abstract: In this study most patients with corneal ulcer presented with poor vision and excessive lacrimation. Trauma was the commonest predisposing factor with bacterial organisms as the commonest isolate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
4
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 20 publications
2
15
4
3
Order By: Relevance
“…This finding is in keeping with the study by Oladigbolu[16] in NorthernTable 2. Microbiological diagnosis.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…This finding is in keeping with the study by Oladigbolu[16] in NorthernTable 2. Microbiological diagnosis.…”
supporting
confidence: 93%
“…Self-medication, patronizing quacks, use of traditional medication all contribute to the delayed presentation with patients reporting to the hospital only after failure of other modalities have been established Oladigbolu et al [16]. All the patients presented blind in the affected eye with visual acuity ranging from light perception to counting fingers at 1 metre.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Post-traumatic abrasions are a common problem in humans in both developed 2 and Third World countries. 3,4 According to the World Health Organization, it is estimated that corneal opacities, including corneal ulceration, are the fourth leading cause of blindness worldwide. 5 The same is true in canine and feline patients where many corneal ulcerations have a traumatic origin and can lead to corneal blindness.…”
mentioning
confidence: 99%
“…[14] A study in Northern Nigeria reported that 0.4% of patients with corneal ulcers were associated with use of contact lenses. [15]…”
Section: Discussionmentioning
confidence: 99%